Effects of the Different Doses of Esketamine on Postoperative Quality of Recovery in Patients Undergoing Modified Radical Mastectomy: A Randomized, Double-Blind, Controlled Trial [Response to Letter] - Zhu M; Xu S; Ju X; Wang S; Yu X (Dove Medical Press, 2023)
Min Zhu, Siqi Xu, Xia Ju, Shengbin Wang, Xitong Yu Department of Anesthesiology, The Anqing Medical Center of Anhui Medical University, The Fifth Clinical Medical College of Anhui Medical University, Anqing, People’s Republic of ChinaCorrespondence: Xia Ju, Department of Anesthesiology, The Anqing Medical Center of Anhui Medical University, The Fifth Clinical Medical College of Anhui Medical University, Anqing, 246003, People’s Republic of China, Tel +86 13685563136, Email alcon2006@126.com